Cost Analysis of Indonesia Case Based Groups (INA-CBGs) Tariff for Stroke Patients - Ingenida Hadning; Fitriannisa Fathurrohmah; Muhammad Ridwan; Bangunawati Rahajeng; Pinasti Utami; Indriastuti Cahyaningsih (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The INA-CBG’s (Indonesia Case Based Groups) package rate implementation for National Health Insurance Program member since 1st January 2014 suffering from stroke has forced all hospitals in Indonesia to do a quality control and efficient service cost. Stroke, one of the catastrophic diseases often accompanied with some of its comorbid factors, requires high treatment cost. Thus, a cost analysis study is needed to prevent hospital loss. This study was aimed at determining the suitability of cost between the real cost of stroke therapy and the Indonesian Case-Based Groups (INA-CBG) rate according to the Ministry of Health Decree number 69 of 2013. This study was an observational study with a cross-sectional design. Data collection was done retrospectively. Study subjects were all that hospitalized strokes of patients who were members of the National Health Insurance and also met the inclusion and exclusion criteria registered between January to June 2014. The study data were in real direct medical costs analyzed for its suitability with the INA-CBG's rate. Descriptive statistical tests and t-tests were used to analyze the data. The results showed that the average real cost of the first-class hospitalization was higher than INA-CBG's rate for cerebral infarction and for unspecified stroke, with insignificant discrepancies. The average real cost of second class hospitalization was lower than INA-CBG's rate for cerebral infarction, otherwise the average cost was higher than INA-CBG's rate for unspecified stroke, with insignificant discrepancies. The average real cost of third class hospitalization was lower than INA-CBG's rate for cerebral infarction and for unspecified stroke, with significant discrepancies. Most of the average costs were higher than the INA-CBG rate. Thus, the hospital is not capable of managing a stroke of cost-based treatment on INA-CBGs. The hospital has suffered losses. INA-CBG's rate of stroke treatment needs to be evaluated.